Implementasi Sistem E-Procurement Pada Layanan Pengadaan Secara Elektronik (LPSE) Provinsi Kepulauan Riau - Rendra Setyadiharja; Achmad Nurmandi (Universitas Muhammadiyah Yogyakarta, 2014)
The purpose of this study is to see how the implementation of e-procurement system via the Electronic ProcurementService (LPSE) Government of Riau Islands province, which had been adopted in 2008. The study also want to seehow they affect the political process towards the implementation of e-procurement. The method in this study is a mixmethod. Data collection techniques used in this research are questionnaires, interviews and documentation. While thegoal of this research is the party who understand in detail how the process of implementing e-procurement system inthe province of Riau Islands. Results from this study is that the implementation of e-procurement system in RiauIslands province has been run very effectively with the effectiveness index value of 3.27. Parameters that contributeto the effectiveness of the implementation is the purpose and the type of website system (3.33), regulation (3.31)clarity of e-procurement planning (3.28), human resources suppor t (3.27), eff iciency and effectiveness ( 3.25),support infrastructure is the lowest parameter with a value of 3.11. At the level of the political process, imlementasi e-procurement system is significantly affected by opportunistic behavior of agent (22.42%), clarity of informationprincipal (16.87%), clarity of information agent (15.37%), principal opportunistic beha vior (13, 40%), principalcontracting mechanisms (13.04%), the mechanism of contract agent (16.30%). Total influence the political processtowards the implementation of e-procurement system in LPSE Riau Islands Province amounted to 97.40% state thathas a very strong influence on the implementation of e-procurement system in LPSE Riau Islands Province. while2,60% influenced by other variables.